Changes in water footprint of crop production in Beijing from 1978 to 2012: a logarithmic mean Divisia index decomposition analysis - Xu, Yanjie; Huang, Kai; Yu, Yajuan; Wang, Xiaomeng (Journal of cleaner production, 2015)
Beijing has been facing increasingly severe water scarcity. Water consumed by crop production is a notable proportion. To estimate total water consumption of crop production in Beijing, we refer to the water footprint concept, taking both direct and indirect water into account. The water footprint (WF) of crop production consists of blue, green and grey components. We use the logarithmic mean Divisia index (LMDI) decomposition method to quantitatively analyze the driving factors for changes in WF. From 1978 to 2012, WF of crop production in Beijing experienced a decrease of 35.1%. This offset primarily resulted from rapid urbanization. The structure and technological factors acted as additional decrease factors. On the contrary, surged population and production scale effect hindered the water conservation process. To further promote water conservation in crop production, we have to continue improving water saving technology and adjusting plantation structure. Crop production in Beijing shows a greater blue WF than the green and grey ones, so rain-fed crops should be further promoted. This work elucidates how diverse determinants affect WF of crop production, which can provide detailed insights into the summary and outlooks of local crop water sustainability. •We figure out WF of crop production in Beijing during 1978–2012.•We examine driving factors for changes in WF with a LMDI approach.•WF experienced an upward stage, a downward stage and a stable stage.•Urbanization, structure and technology effect took down WF of crop production.•Surged population and production scale effect hindered water conservation.